'Specific Normalization' method for NIRS calibrations. Issue 3 (June 2023) - Cayuela-Sánchez, José Antonio
In this study, we present a chemometric procedure called 'Specific Normalization'. It upgrades the calibration for use in a specific set of new samples by normalizing together the spectra of both the calibration set and a new measured sample set. The proposed procedure is shown for near infra-red spectroscopy measurement of olive oil acidity, as an example. This procedure would need its integration as software application for routine analysis.